A multi‐component method to determine pesticides in surface water by liquid‐chromatography tandem quadrupole mass spectrometry. (15th June 2017) - Ramos, A. M.; Whelan, M. J.; Cosgrove, S.; Villa, R.; Jefferson, B.; Campo, P.; Jarvis, P.; Guymer, I.
Abstract: Pesticide pollution of surface water is a major concern in many agricultural catchments The development of rapid and accurate methods for determining pesticide concentrations in water samples is, therefore, important. Here we describe a method for the simultaneous analysis of six pesticides (metaldehyde, quinmerac, carbetamide, metazachlor, propyzamide and pendimethalin) in natural waters by direct aqueous injection with liquid chromatography‐tandem mass spectrometry. The method validation showed good linearity from 0.2 to 50.0 µg/L with correlation coefficients between 0.995 and 0.999. Method accuracy ranged from 84 to 100% and precision Relative standard deviation (RSD) from 4 to 15%. The limits of detection for the targeted pesticides ranged from 0.03 to 0.36 µg/L. No significant matrix effects on quantification were observed ( t ‐test). The method was tested on water samples from a small arable catchment in eastern England. Peak concentrations for the determinands ranged from 1 to 10 µg/L.